Secondhand smoke in combination with ambient air pollution exposure is associated with increasedx CpG methylation and decreased expression of IFN-γ in T effector cells and Foxp3 in T regulatory cells in children - Kohli, Arunima; Garcia, Marco A; Miller, Rachel L; Maher, Christina; Humblet, Olivier; Hammond, S Katharine; Nadeau, Kari (Clinical epigenetics, 2012)
Secondhand smoke (SHS) and ambient air pollution (AAP) exposures have been associated with increased prevalence and severity of asthma and DNA modifications of immune cells. In the current study, we examined the association between SHS and AAP with DNA methylation and expression of interferon-gamma (IFN-γ) and forkhead box protein 3 (Foxp3) in T cell populations. Subjects 7-18 years old were recruited from Fresno (high AAP; n = 62) and Stanford, CA (low AAP; n = 40) and divided into SHS-exposed (Fresno: n = 31, Stanford: n = 6) and non-SHS-exposed (nSHS; Fresno: n = 31, Stanford: n = 34) groups. T cells purified from peripheral blood were assessed for levels of DNA methylation and expression of IFN-γ (in effector T cells) or Foxp3 (in regulatory T cells). Analysis showed a significant increase in mean % CpG methylation of IFN-γ and Foxp3 associated with SHS exposure (IFN-γ: FSHS 62.10%, FnSHS 41.29%, p < 0.05; SSHS 46.67%, SnSHS 24.85%, p < 0.05; Foxp3: FSHS 74.60%, FnSHS 54.44%, p < 0.05; SSHS 62.40%, SnSHS 18.41%, p < 0.05) and a significant decrease in mean transcription levels of both genes (IFN-γ: FSHS 0.75, FnSHS 1.52, p < 0.05; SHS 2.25, nSHS 3.53, p < 0.05; Foxp3: FSHS 0.75, FnSHS 3.29, p < 0.05; SSHS 4.8, SnSHS 7.2, p < 0.05). AAP was also associated with hypermethylation (IFN-γ: FSHS vs. SSHS, p < 0.05; FnSHS vs. SnSHS, p < 0.05; Foxp3: FSHS vs. SSHS, p < 0.05; FnSHS vs. SnSHS, p < 0.05) and decreased transcription of both genes (IFN-γ: FSHS vs. SSHS, p < 0.05; FnSHS vs. SnSHS, p < 0.05; Foxp3: FSHS vs. SSHS, p < 0.05; FnSHS vs. SnSHS, p < 0.05). Average methylation between AAP- and SHS-only exposures was not significantly different (IFN-γ: p = 0.15; Foxp3: p = 0.27), nor was Foxp3 expression (p = 0.08); IFN-γ expression was significantly decreased in AAP-only subjects (p < 0.05). Exposures to SHS and AAP are associated with significant hypermethylation and decreased expression of IFN-γ in Teffs and Foxp3 in Tregs. Relative contributions of each exposure to DNA modification and asthma pathogenesis warrant further investigation.